2002
DOI: 10.1038/sj.onc.1205134
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p73 by c-Abl through the p38 MAP kinase pathway

Abstract: p73 is a novel member of the p53 family of tumor suppressor proteins which is involved in cellular dierentiation, tumor suppression, and the response to genotoxic stress. The molecular mechanisms regulating p73 activity are still poorly understood. Recently, p73 was found to be a target of the enzymatic activity of c-Abl, a non-receptor tyrosine kinase that potently activated in response to DNA damage. Here, we present evidence that c-Abl induces the phosphorylation of p73 in threonine residues adjacent to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 31 publications
1
70
0
Order By: Relevance
“…c-Abl activated by cisplatin can also upregulates the MEKK-MKK-JNK pathway (Kharbanda et al, 2000), but the implied association between this specific MAPK pathway and p73 has been uncertain previously. However, the case for this association has been strengthened by recent evidence, which shows that activation of p73 by c-Abl also requires the activity of p38 as a representative of the MAPK subfamily member (Sanchez-Prieto et al, 2002).…”
Section: Induction Of Apoptosismentioning
confidence: 95%
“…c-Abl activated by cisplatin can also upregulates the MEKK-MKK-JNK pathway (Kharbanda et al, 2000), but the implied association between this specific MAPK pathway and p73 has been uncertain previously. However, the case for this association has been strengthened by recent evidence, which shows that activation of p73 by c-Abl also requires the activity of p38 as a representative of the MAPK subfamily member (Sanchez-Prieto et al, 2002).…”
Section: Induction Of Apoptosismentioning
confidence: 95%
“…Gemcitabine has also been shown to activate p38 MAPK (56). c-Abl phosphorylates, stabilizes, and activates p73 and, moreover, the p38 MAPK cascade mediates this response (23,57). Because p73 has also recently been implicated in c-Abl induction of apoptosis following DNA damage (23), it was for 2 h, washed, and incubated in fresh medium for an additional 24 h. Cell lysates were fractionated on SDS-PAGE gels and were analyzed by Western blotting using antibodies against p73, p53, and actin.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, c-Abl kinase may provide an explanation. It has been found that c-Abl can activate p38 through MKK6 [72][73][74] , and JNK by translocating from nucleus to cytoplasm to phosphorylate hematopoietic progenitor kinase (HPK1), an upstream kinase of JNK [75] . Therefore, c-Abl may fulfill a role as the message carrier to transduce signals between subcellular locations.…”
Section: Regulation Of the Tumor Suppressor P53 Proteinmentioning
confidence: 99%